`(2x^3-4x^2-15x+5)/(x^2-2x-8)`

Since the above rational expression is an improper rational expression , so the first step is to divide and express the expression as a sum of simpler fractions such that the degree of the polynomial in the numerator is less than the degree of the polynomial in the denominator.

Dividing the polynomial using long division method yields,

`(2x^3-4x^2-15x+5)/(x^2-2x-8)=2x+(x+5)/(x^2-2x-8)`

Since the polynomials do not completely divide, we have to continue with the partial fractions of the remainder expression,

Now let's factorize the denominator of the remainder expression,

`x^2-2x-8=x^2-4x+2x-8`

`=x(x-4)+2(x-4)`

`=(x+2)(x-4)`

Let,`(x+5)/(x^2-2x-8)=A/(x+2)+B/(x-4)`

`=(A(x-4)+B(x+2))/((x+2)(x-4))`

`=(Ax-4A+Bx+2B)/((x+2)(x-4))`

`=(x(A+B)-4A+2B)/((x+2)(x-4))`

`:.(x+5)=x(A+B)-4A+2B`

Equating the coefficients of the like terms,

`A+B=1` ----- equation 1

`-4A+2B=5` ------ equation 2

Now solve the above equations to get the solutions of A and B,

From equation 1,

`A=1-B`

substitute the above expression of A in equation 2 ,

`-4(1-B)+2B=5`

`-4+4B+2B=5`

`6B=5+4`

`B=9/6`

`B=3/2`

Plug the value of B in equation 1,

`A+3/2=1`

`A=1-3/2`

`A=-1/2`

`(x+5)/(x^2-2x-8)=-1/(2(x+2))+3/(2(x-4))`

`:.(2x^3-4x^2-15x+5)/(x^2-2x-8)=2x-1/(2(x+2))+3/(2(x-4))`

You need to decompose the fraction in simple irreducible fractions, such that:

`(2x^3 - 4x^2 - 15x + 5)/(x^2 - 2x - 8) = (2x^3 - 4x^2 - 15x + 5)/((x-4)(x+2))`

`(2x^3 - 4x^2 - 15x + 5)/((x-4)(x+2)) = A/(x-4) + B/(x+2)`

You need to bring to the same denominator all fractions, such that:

`2x^3 - 4x^2 - 15x + 5 = A(x+2) + B(x-4)`

`2x^3 - 4x^2 - 15x + 5 = Ax + 2A + Bx - 4B`

You need to group the terms having the same power of x:

`2x^3 - 4x^2 - 15x + 5 = x(A+B) + 2A - 4B`

Comparing the expressions both sides yields:

`A + B =-15 => A = -15 - B `

`2A - 4B = 5 => 2(-15 - B) - 4B = 5 => -30 - 2B - 4B = 5 => -6B = 35 => B = -35/6`

`A = 15 + 35/6 => A = 125/6`

**Hence, the partial fraction decomposition of the improper rational expression is `(2x^3 - 4x^2 - 15x + 5)/((x-4)(x+2)) = 125/(6(x-4)) - 35/(6(x+2))` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now